2003
DOI: 10.1159/000072884
|View full text |Cite
|
Sign up to set email alerts
|

Auditory-Evoked Potentials and Selective Attention: Different Ways of Information Processing in Cannabis Users and Controls

Abstract: The present study tested the hypothesis that chronic cannabis use leads to persistent attentional dysfunctions and that age of onset of cannabis use is a potential predictor of impaired test performance and information processing. Brain event-related potentials (ERPs) during a complex auditory selective attention task were recorded from 21 cannabis users divided into two groups according to age of onset and from 13 controls comparable with respect to age, IQ and educational background. Participants were instru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
57
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 22 publications
8
57
0
1
Order By: Relevance
“…For example, introduction of cannabis during adolescence may interrupt pruning of gray matter or disruption of white matter myelination, especially in the prefrontal cortex (Block et al, 2002;Egerton et al, 2006;Lundqvist et al, 2001), which continues to develop into early adulthood (Gogtay et al, 2004;Lenroot & Giedd, 2006;Nagel et al, 2006;Sowell et al, 2004). The current findings are consistent with animal studies that found more severe cannabis-induced learning impairments among adolescents compared with adults (Cha et al, 2006;Schneider & Koch, 2003;Stiglick & Kalant, 1982, 1985 and findings that early onset use is associated with increased morphometric, electrophysiological, and cognitive abnormalities among adult marijuana users (Ehrenreich et al, 1999;Kempel et al, 2003;Pope et al, 2003;Wilson et al, 2000). It is unknown whether continued abstinence from marijuana results in neurocognitive recovery or subsequent healthy neurodevelopment among adolescents.…”
Section: Discussionsupporting
confidence: 85%
“…For example, introduction of cannabis during adolescence may interrupt pruning of gray matter or disruption of white matter myelination, especially in the prefrontal cortex (Block et al, 2002;Egerton et al, 2006;Lundqvist et al, 2001), which continues to develop into early adulthood (Gogtay et al, 2004;Lenroot & Giedd, 2006;Nagel et al, 2006;Sowell et al, 2004). The current findings are consistent with animal studies that found more severe cannabis-induced learning impairments among adolescents compared with adults (Cha et al, 2006;Schneider & Koch, 2003;Stiglick & Kalant, 1982, 1985 and findings that early onset use is associated with increased morphometric, electrophysiological, and cognitive abnormalities among adult marijuana users (Ehrenreich et al, 1999;Kempel et al, 2003;Pope et al, 2003;Wilson et al, 2000). It is unknown whether continued abstinence from marijuana results in neurocognitive recovery or subsequent healthy neurodevelopment among adolescents.…”
Section: Discussionsupporting
confidence: 85%
“…Long-term heavy cannabis users show impairments in attention that endure beyond the period of intoxication and worsen with increasing years of regular cannabis administration (Solowij, Stephens et al 2002). Studies examining the effects of cannabinoids on attention, utilizing a combination of performance and event-related potential measures, have shown that chronic cannabis use affects information processing (Kempel, Lampe et al 2003). Specifically, cannabis consumers are unable to filter out extraneous information and there is an inability to effectively focus attention and reject irrelevant information (Solowij, Michie et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…A longitudinal study of marijuana dependent adolescents demonstrated further shortterm memory decrements that persisted after 6 weeks of monitored abstinence (Schwartz et al, 1989). In addition, compared to individuals with adult-onset cannabis use disorder and nonabusing controls, adolescent-onset cannabis use disordered adults showed attenuated electrophysiological response during selective attention (Kempel et al, 2003), as well as smaller frontal and parietal volumes and increased cerebral blood flow (Wilson et al, 2000). These studies indicate that heavy marijuana use during youth may adversely affect cognition and brain functioning, particularly short-term memory and attention, and raise questions about the integrity of frontal and parietal brain regions in adolescents with marijuana use disorders.…”
Section: Introductionmentioning
confidence: 99%